Vacancy tetrahedra in copper due to electron Irradiation in the high-voltage microscope. - Ipohorski, M.; Spring, M. S. (Taylor & Francis, 1970)
Fil: Ipohorski, M. Comisión Nacional de Energía Atómica; Argentina